Bi-frontal transcranial alternating current stimulation in the ripple range reduced overnight forgetting - Ambrus, Géza Gergely; Pisoni, Alberto; Primaßin, Annika; Turi, Zsolt; Paulus, Walter; Antal, Andrea (Frontiers in Cellular Neuroscience, 2015)
High frequency oscillations in the hippocampal structures recorded during sleep have been proved to be essential for long-term episodic memory consolidation in both animals and in humans. The aim of this study was to test if transcranial Alternating Current Stimulation (tACS) of the dorsolateral prefrontal cortex (DLPFC) in the hippocampal ripple range, applied bi-frontally during encoding, could modulate declarative memory performance, measured immediately after encoding, and after a night’s sleep. An associative word-pair learning test, taken from Marshall and colleagues, was used. During an evening encoding phase, participants received 1 mA 140 Hz tACS or sham stimulation over both DLPFCs for 10 minutes while being presented twice with a list of word-pairs. Cued recall performance was investigated 10 minutes after training and the morning following the training session. Forgetting from evening to morning was observed in the sham condition, but not in the 140 Hz stimulation condition. 140 Hz tACS during encoding may have an effect on the consolidation of declarative material.